Interaktives Notfalltraining in der Zahnmedizin: Entwicklung einer Virtual Patient Player- Simulationssoftware. - Geneit, Martin (GMS Medizinische Informatik, Biometrie und Epidemiologie, 2018)
Virtual patients have long been established as part of medical training. With their help, students can develop their therapeutic and diagnostic skills under conditions that are as realistic as possible, without any risk for a patient. While model or dummy simulations represent a standard in dentistry for the training of manual skills, computer-based, interactive simulations of virtual patient cases in this field are rarely described. Some of these systems have been designed for a limited purpose and do not permit a flexible and reusable design of virtual patients, or only permit it with restrictions. The MedBiquitous standard offers solutions for this purpose. This has proven itself in the medical field as a basis for virtual patient simulations. It offers an expandable structure for the data of virtual patients and describes fundamental algorithms of associated simulation software. In this paper, virtual patient player simulation software for interactive emergency training in dentistry is developed on the basis of the MedBiquitous model. As an example, a first virtual patient was created. MedEmergency Player enables action-focussed simulation without rigidly predefined linear or branched treatment pathways, unlike existing systems and the previous use of the MedBiquitous standard. The user directly experiences and examines the reactions as with a real patient